DNA methylation and bronchiectasis: a Mendelian randomization analysis to investigate causal link and therapeutic target - Jiangyue Qin; Bi Ran; Lian Liu; Ping Li; Zhenni Chen; Diandian Li; Yongchun Shen; Fuqiang Wen (Epigenetics)
This study aims to discover drug targeted genes and explore the potential epigenetics mechanisms in bronchiectasis. Cis-expression quantitative trait locus (eQTL) was obtained as exposure, and bronchiectasis from the FinnGen cohort was used as outcome. Mendelian Randomization (MR) was performed to identify therapeutic targets associated with bronchiectasis. Colocalization and summary-data-based MR (SMR) analyses were carried out to further confirm the causal roles of candidate genes in bronchiectasis. The value of these drug targets was validated via drug prediction and molecular docking. Finally, we used mediation analysis to identify the DNA methylation QTLs to bronchiectasis mediated by candidate genes. Ten drug targets were significantly associated with bronchiectasis. Strong evidence for the colocalization of ACVR2A and VRK2 with bronchiectasis was found (PP.H4 > 0.75). SMR analysis revealed that higher expressions of DDR1 and VRK2 were linked to a higher risk of bronchiectasis, and higher expressions of SCD5, TNFRSF4 and XCL2 were linked to a lower risk of bronchiectasis. Finally, mediation analysis revealed potential causality effect of the DNA methylation site cg21568453 to bronchiectasis risk via VRK2. The increased expression of VRK2 regulated by DNA methylation at cg21568453 may promote the occurrence of bronchiectasis.